Improving Water and Sanitation Services in Colombian Muncipalities through Private Operators - Libhaber, Menahem (World Bank, Washington, DC, 2012)
This brief includes the following headings: introduction; building on experience - scaling up; two sizes, two approaches; results on the ground; ensuring provision of services to the poor; beyond the project; conclusion; lessons learned; about the authors; and about 'en breve'.